2008
DOI: 10.1111/j.1439-0388.2008.00730.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity in Egyptian and Italian goat breeds measured with microsatellite polymorphism

Abstract: Seven microsatellite markers were used to study genetic diversity of three Egyptian (Egyptian Baladi, Barki and Zaraibi) and two Italian (Maltese and Montefalcone) goat breeds. The microsatellites showed a high polymorphic information content (PIC) of more than 0.5 in most of the locus-breed combinations and indicated that the loci were useful in assessing within- and between-breed variability of domestic goat (Capra hircus). The expected heterozygosity of the breeds varied from 0.670 to 0.792. In the geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
32
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 26 publications
7
32
10
Order By: Relevance
“…Therefore the loci examined in this study were highly informative. The mean number of alleles per loci (13.33) were higher than those reported by Saitbekova et al 38 , Agha et al 39 Genetic Diversity of Three ... et al 40 , Fatima et al 41 , Oliveira et al 42 , Qi et al 43 , lower than those reported by Serrano et al 33 , Caňón et al 44 and similar to those reported by Missohou et al 37 , Barker at al. 45 , Chenyambuga et al…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Therefore the loci examined in this study were highly informative. The mean number of alleles per loci (13.33) were higher than those reported by Saitbekova et al 38 , Agha et al 39 Genetic Diversity of Three ... et al 40 , Fatima et al 41 , Oliveira et al 42 , Qi et al 43 , lower than those reported by Serrano et al 33 , Caňón et al 44 and similar to those reported by Missohou et al 37 , Barker at al. 45 , Chenyambuga et al…”
Section: Discussioncontrasting
confidence: 53%
“…Observed and expected heterozygosities estimated in this study were higher than those found in most studies 12,38,39,52,53,[57][58][59] . The values were also higher than those reported for Abaza (0.772), Angora (0.750), Gurcu (0.751) and Hair goat breeds (0.722) raised in Turkey 43 .…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…On the other hand, the most known goat breed in Syria is the Damascus goat, known sometimes as Shami. In other nearby countries, the common native goat breed is the Black Bedouin in Palestine (Silanikove, 1986) and Egyptian Baladi or Bedouin goat in Egypt (Agha et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Microsatellites have been commonly utilized for the assessment of genetic diversity, construction of genetic maps, quantitative trait loci mapping and parentage testing etc. (Batendse et al 1997, Buchanan et al 1994, Jin et al 2005, Agha et al 2008, Manatrinon et al 2008, Ślaska et al 2008, Kusza et al 2010. Li et al (2002) analyzed genetic relationships among twelve Chinese indigenous goat populations based on 26 microsatellite markers.…”
Section: Introductionmentioning
confidence: 99%